Flow Synthesis of Substituted γ‐Lactones by Consecutive Photocatalytic/Reductive Reactions. Issue 4 (3rd March 2014) - Fagnoni, Maurizio; Bonassi, Filippo; Palmieri, Alessandro; Protti, Stefano; Ravelli, Davide; Ballini, Roberto
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>